Verkehrserhebungen. Organisationsformen einer wirtschaftlichen Durchführung. - Moik, Peter (Deutscher Verkehrs-Verlag, 2004)
Durch die Wahl einer geeigneten Organisationsmethode der Feldarbeit lassen sich erhebliche Einsparungen bei Verkehrserhebungen erzielen. Die verschiedenen Möglichkeiten zur Betreuung der Feldarbeit werden in dem Beitrag genannt und Auswahlkriterien einer geeigneten Organisationsmethode vorgestellt. difu

Choosing a suitable organizational method to carry out traffic surveys may lead to notable cost savings. The need for different types of traffic surveys from the aspect of organization can be compared and generalized: in all cases, personnel has to be recruited, taken on, trained, delegated for specific duties, looked after and supervised. While it is possible to standardize methods to advertise for, take on, and train, the staff neeed, it is advantageous to apply different organizational methods by taking into account the size of the area under survey and the number of staff required. In such cases, surveys can be handled on a local basis while separate offices can be set up to help evaluate the findings. Wherever large areas have to be surveyed, suitable alternatives involve mailing the forms needed or relying on the Internet for support, which allows better control of the survey work. By choosing a suitable organizational form that meets local requirements, a notable reduction in overhead costs may be achieved. difu
Keywords: Verkehrsplanung; Verkehr; Erhebung; Erhebungsmethode; Ablauforganisation; Personaleinsatz; Organisationsform; Untersuchungsgebiet; Verkehrserhebung; Verkehrsdaten; Qualitätssicherung